2017
DOI: 10.1007/s11325-017-1475-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and carbonyl stress in pregnant women with obstructive sleep apnea

Abstract: Contrary to our hypothesis, the results of this study suggest that pregnant women with OSA have higher antioxidant capacity and lower oxidative and carbonyl stress markers compared to controls, suggesting a possible protective effect of intermittent hypoxia. Whether OSA in pregnancy impacts oxidative stress differently than OSA in the general population remains to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…8-Hydroxy-2-deoxyguanosine (8-OHdG) is a product derived from the oxidation of deoxyribonucleic acid (DNA) used in the literature to evaluate oxidative stress damage [ 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Several studies have reported a correlation between the severity of OSAS and 8-OHdG, as well as the total antioxidant capacity (TAC) [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8-Hydroxy-2-deoxyguanosine (8-OHdG) is a product derived from the oxidation of deoxyribonucleic acid (DNA) used in the literature to evaluate oxidative stress damage [ 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Several studies have reported a correlation between the severity of OSAS and 8-OHdG, as well as the total antioxidant capacity (TAC) [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported a correlation between the severity of OSAS and 8-OHdG, as well as the total antioxidant capacity (TAC) [ 68 ]. Moreover, urinary excretion (8-OHdG) has been positively correlated in patients with OSAS [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…69,70 However, preliminary data show flattening, rather than activation, of the cortisol awakening response. 59 Other potential mechanisms include an enhanced inflammatory profile, endothelial dysfunction, and oxidative stress but remain to be proven; recent data, however, suggest that oxidative stress may not be implicated 71 given potential downregulation by estradiol. 23 The allostatic load hypothesis has also been proposed, suggesting that chronic sleep loss is both a precipitant of stress as well as a consequence of it, leading to a stress "overload" that may account for adverse pregnancy outcomes.…”
Section: Sleep In Pregnancymentioning
confidence: 99%
“…Khan et al conducted a case-controlled analysis of serum markers of oxidative stress and antioxidant capacity in women with OSA in pregnancy and, contrary to their hypotheses, found that the pregnant women with OSA had a significantly greater antioxidant capacity and lower oxidative and carbonyl stress markers than controls. [68]…”
Section: The Pathogenesis Of Osa and Hypertensive Disorders Of Pregnancymentioning
confidence: 99%